ENHANCING WRITING CREATIVITY THROUGH BLENDED LANGUAGE LEARNING: INSIGHTS FROM POETRY 5.0 - Budiawan, Budiawan; Agus, Cecep (University of Kuningan, 2025)
The study looks at using poetry 5.0 learning with blended language learning (BLL) to boost students' creativity and writing skills. A qualitative approach was taken, using virtual ethnography and classroom research, with data gathered through observations, interviews, and looking at student work. The findings show that BLL-based poetry 5.0 creates a lively and engaging learning space that encourages creativity, critical thinking, and emotional expression. Visual prompts and digital tools, especially Instagram, allowed students to connect personal experiences and get quick feedback from classmates and teachers. This method improved students’ ability to share ideas, think about social issues, and create unique poetry. However, the study encountered some issues like limited face-to-face interaction, which point out areas for teaching improvement. Overall, combining poetry 5.0 with BLL shows promise as a creative teaching method that meets the needs of society 5.0. More research is suggested to look into its use in different educational settings.